SIFAT-SIFAT ISOMORFISMA GRAF FUZZY PADA GRAF FUZZY KUAT - Handayani, Anik; Ratnasari, Lucia (MATEMATIKA, 2012)
Fuzzy graph is a graph consists pairs of vertex and edge that have degree of membership containing closed interval of real number [0,1] on each edge and vertex. A fuzzy graph is said to be a strong fuzzy graph if degree of membership edge with the same minimum degree of membership vertex and degree of membership vertex for each edge with . In this paper describes the properties of fuzzy graphs isomorphism include weak isomorphism, co-weak isomorphism, and isomorphism on strong fuzzy graph.